A Walk on the Wild Side: 2018 Cool-Season Forage Recommendations for Wildlife Food Plots in North Florida - A. R. Blount; M. Wallau; H. K. Ober; E. Rios; J. M. B. Vendramini; J. C. B. Dubeux; Md. A. Babar; C. L. Mackowiak; K. H. Quesenberry (EDIS)
Forage variety recommendation for wildlife.